Digestibilidad in situ de rastrojo de maíz tratado con enzimas fibrolíticas - López Inzunza, Hugo de Jesús; Chongo García, Bertha Bienvenida; La O-León, Orestes; Guerra Liera, Juan Eulogio; Luna López, Maribel; Castro Camacho, Samuel Jesús; López Juárez, Luciano Abelino (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 31-37